ICT advancements and its undesired ramifications - Ansari, Abdul Haseeb (Science Publishing Corporation Inc, 2018)
Information and communication technology (ICT) has the credit to be relatively more closely related to the society facilitating economic transactions to be easy and fast and social wellbeing in all walks of life. It has had global and international importance, as it has worked as an important tool in globalizing the world, and has become a pressing necessity of the globalized world. Moreover, its relevance in the globalized world is intensifying, as its constructive role is every day spiraling. Its vale in that sense will go on mounting. On the other hand, its evil-ridden uses and abuses are menacing the people and countries around the world. Delinquent people and rogue countries are using the technology for achieving their sinister objectives. This aspect of the technology is bothering policymakers, business executives and individuals in the society. In view of this, two pertinent questions arise: one, which of the two aspects of the information and communication technology is dominant; and second, what preventive and punitive measures should we adopt in order to mitigate the evil use of the technology. A vivid comparison of both, which has been carried out in the paper, demonstrates that the beneficial use of the information and communication technology is predominantly high. Thus, our strategy, as the paper suggests, should be to support the useful aspect of the technology with useful conditionality so that it could abate and control its evil use, and to adopt preventive and punitive measures in order to defeat the evil-doers. For that, both legal and extralegal tools should be adhered to. Towards these, the paper offers some useful suggestions.